The Diagnostic Value of Automated Neutrophil and Monocyte Parameters in Early Recognition of Sepsis - Bansal, Taruna; Yadav, Sonal; Rakheja, Garima; Kumar, Vijay (Annals of Pathology and Laboratory Medicine, 2025)
Background: Sepsis is a medical emergency. Treatment for sepsis is effective only if started early, and a critical lapse of time may be detrimental. The existing blood biomarkers for sepsis, like CRP and Procalcitonin, suffer from cost-ineffectiveness and an additional sample to be handled. The Leukocyte Cell Population Data (CPD) include NEU-X, NEU-Y, MON-X, and MON-Y. NEU-X measures the structural complexity of neutrophils by sideward scatter (SSC), while NEU-Y measures the DNA and RNA content by sideward fluorescence light. Our study aimed to evaluate the utility and significance of NEU-X and NEU-Y in the early diagnosis of sepsis. Methods: It was a prospective, observational study done over a period of one month at a tertiary care hospital, which included 300 participants admitted in the ICU: 150 adults with suspected sepsis and 150 healthy controls. Blood samples were collected in EDTA vials and run on a Sysmex XN-1000 automated hematology analyser for CBC (complete blood counts) and values of NEU-X, NEU-Y, MON-X, and MON-Y parameters. Results: The median value of NEU-X, NEU-Y, and MON-Y demonstrated a significant p-value of <0.0001 between cases and controls. NEU-X had a sensitivity of 79.33% and specificity of 91.33% at a cut-off of >339, while NEU-Y exhibited sensitivity and specificity of 93.33% each at a cut-off of >727. MON-Y and MON-X had a cut-off value of ≤90.3 and ≤118.9, respectively. Conclusion: The leukocyte CPD parameters-NEU-X, NEU-Y, and MON-Y-represent a promising set of data and can be helpful in the early diagnosis of sepsis.